Optimisation of hybrid energy systems for maritime vessels. Issue 17 (26th April 2019) - Tang, Wenshuo; Dickie, Ross; Roman, Darius; Robu, Valentin; Flynn, David
Abstract : The decarbonisation agenda in maritime transport requires that asset owners and operators adopt greener technologies within their existing and new vessels. The primary drivers within this agenda relate to improved environmental metrics, efficient energy performance, and improved asset management. However, the integration of new technologies always presents technical and financial risks. Here, utilising energy and environmental monitoring from real vessels, the authors propose an energy system optimisation architecture, hybrid fusion energy management system (HyFES), that optimises the key performance indicators of energy performance, reduction of diesel engine nitrogen oxide (NOx), and particulate matter (PM), and prognostic state of health assessment of energy storage technologies. Using state of the art machine‐learning techniques, the authors are able to determine the on‐board lithium‐ion and lead acid batteries' state of health with accuracy > 8 and 4%, respectively. Dependent on the mode of operation, optimisation of energy performance indicates fuel saving of between 70 and 80% for the vessel operator. Future research will focus on the integration of more assets into the optimisation architecture and increased vessel journey use cases.